2005
DOI: 10.1021/jm050060l
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV Activity of (−)-(2R,4R)-1- (2-Hydroxymethyl-1,3-dioxolan-4-yl)- thymine against Drug-Resistant HIV-1 Mutants and Studies of Its Molecular Mechanism

Abstract: (-)-(2R,4R)-1-(2-Hydroxymethyl-1,3-dioxolan-4-yl)thymine (DOT) is the first thymidine kinase-activated nucleoside that is significantly active against all of the clinically significant NRTI-resistant HIV-1 mutants, including AZT (D67N/K70R/T215Y/K219Q), Tenofovir (K65R), and Lamivudine (M184V). To understand the molecular mechanism of drug resistance and the antiviral activity of DOT against drug-resistant RTs, molecular modeling studies of DOT-TP complexed with the wild-type (WT) and mutated RT were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…327 Dioxolane nucleus is also a prominent structural motif found in synthetic compounds with vital medicinal value. [328][329][330] In 1985, Yalpani and Wilke reported that the products formed in the reaction of ninhydrin with silylating agents varied depending on the silylating agent used. 331 Thereafter, in another strategy, treatment of ninhydrin 1 with chlorotrialkylsilane allows for access to a racemic silylated ninhydrin dimer 284 accompanied with bis(trialkylsilyloxy) derivatives 283 (Scheme 89).…”
Section: Dioxolanesmentioning
confidence: 99%
“…327 Dioxolane nucleus is also a prominent structural motif found in synthetic compounds with vital medicinal value. [328][329][330] In 1985, Yalpani and Wilke reported that the products formed in the reaction of ninhydrin with silylating agents varied depending on the silylating agent used. 331 Thereafter, in another strategy, treatment of ninhydrin 1 with chlorotrialkylsilane allows for access to a racemic silylated ninhydrin dimer 284 accompanied with bis(trialkylsilyloxy) derivatives 283 (Scheme 89).…”
Section: Dioxolanesmentioning
confidence: 99%
“…PEG has been used extensively because it extends the half-life of most proteins and results in a greatly increased plasma presence (Greenwald, 2001 (Caliceti et al, 1999;Monfardini et al, 1995;Calogerpoulou et al, 2003). The successful application of α-interferon pegylation by ScheringPlough (PEG-INTRON®;molecular weight of PEG 12 kDa daltons;Takacs et al, 1999) and HoffmanLaRoche (Pegasys®;molecular weight of PEG 40 kDa;Bailon PS & Palleroni AV [1997] We (Chong & Chu 2004;Chu et al, 2005) …”
Section: A Nanoparticle Drug-delivery System Is a Device In Which A Dmentioning
confidence: 99%
“…However, (Bodanszky & Kwei, 1978). PAMAM dendrimers of DOT with phosphate linkers have exhibited a greater antiviral activity (compounds 5, 6 and 7 were 140-, 5-and 56-fold, respectively) (Chu et al, 2005) …”
Section: Antiviral Assays the Procedures For The Antiviral Assays Inmentioning
confidence: 99%
“…1). D-DOT demonstrated potent activity in human PBM cells against lamivudine-resistant (M184V) (EC 50 ϭ 0.088 to 0.2 M), tenofovir-resistant (K65R) (EC 50 ϭ 0.21 M), didanosine-resistant (L74V) (EC 50 ϭ 0.33 M), and zidovudine-resistant (thymidine analog mutations) (EC 50 ϭ 0.49 M) viruses (13,15,16). D-DOT-triphosphate also demonstrated activity against wild-type HIV-1 reverse transcriptase and reverse transcriptases of various mutants, including those of thymidine analog mutants and the M184V mutant, in an enzymatic study (27).…”
mentioning
confidence: 99%
“…D-DOT-triphosphate also demonstrated activity against wild-type HIV-1 reverse transcriptase and reverse transcriptases of various mutants, including those of thymidine analog mutants and the M184V mutant, in an enzymatic study (27). The activity of dioxolane nucleoside triphosphate against many resistant HIV-1 strains may be due to reduced steric hindrance at the active site and to a specific interaction of the 3Ј-oxygen atom with nearby enzyme through H bonding (13,15,16). D-DOT, like AZT and 3Ј-deoxy-2Ј,3Ј-didehydrothymidine (stavudine [D4T]), is also a thymidine analogue that requires cellular TK for activation.…”
mentioning
confidence: 99%